THE NATURE OF LITERARY STUDY AFTER THE RISE OF CONTEMPORARY LITERARY THEORY - Sutanto, Dian Natalia (Sanata Dharma University, 2018)
Before the rise of contemporary literary theory, literary study mainly concerned with the nature, role, function of literary works and general schema for literary criticism. The rise of contemporary literary theories, such as structuralism, poststructuralism, psychoanalysis, feminism, new historicism, postcolonialism, and so on have changed the nature of literary study. By applying concepts and paradigms taken from other spheres of intellectual activity, such as culture, linguistics, aesthetics, politics, history, psychology, economics, gender, and so on, current literary study starts questioning and criticizing literary study basic assumptions. Contemporary literary theory brings a broad array of fundamental issues to attention, such as the act of reading, interpretative strategy, epistemology of literary scholarships, nationalism, genre, gender, originality, intertextuality, social hegemony, authorial intention, truth, representation and so on.DOI: https://doi.org/10.24071/ijhs.2018.020109